Ventral tegmental area dopaminergic action in music therapy for post-traumatic stress disorder: A literature review - Ning, Meng; Wen, Shizhe; Zhou, Peiling; Zhang, Changzheng (Frontiers in Psychology, 2022)
Post-traumatic stress disorder (PTSD) is a debilitating sequela of extraordinary traumatic sufferings that threaten personal health and dramatically attenuate the patient’s quality of life. Accumulating lines of evidence suggest that functional disorders in the ventral tegmental area (VTA) dopaminergic system contribute substantially to PTSD symptomatology. Notably, music therapy has been shown to greatly ameliorate PTSD symptoms. In this literature review, we focused on whether music improved PTSD symptoms, based on VTA dopaminergic action, including the effects of music on dopamine (DA)-related gene expression, the promotion of DA release and metabolism, and the activation of VTA functional activities. In addition, the strengths and limitations of the studies concerning the results of music therapy on PTSD are discussed. Collectively, music therapy is an effective approach for PTSD intervention, in which the VTA dopaminergic system may hold an important position.